Geositesto Be Used In Terms Of Geotourism in Muş Province and Its Surroundings - Dölek, İskender; Şaroğlu, Fuat (Fırat University, 2017)
There are a number of important geosites in terms of geotourism in Muş province and its surroundings. Hamurpet Lake is among important geosites in terms of volcanic and tectonic movements, which are effective in formation of the geosites, and it is located within the boundaries of Muş province. Fossils on Muş-Varto highway, Bingöl and Nemrutvolcanos, Solhan obsidian deposits and Mercimekkale DOM in Sergen rhyolites are signifi cant geosites with their geologic history and cultural values. Muş Overthrust Zone (MOZ) and Varto Fault Zone (VFZ) near Northern Anatolia and Eastern Anatolia Faults; and geologic and geomorphologic formations on these zones are the geosites in Muş provinces and its surroundings.  Geoparks that can be designed by the use of geosites taking place in Muş province and its surroundings can bring significant contributions in socio-economic sense since these geoparks will be not only a place including solely geologic beauties, natural wealth and unique formations, but also manageable and/or operable areas created with a new perspective. They will help both natural and international promotion of the city. This study aims to introduce some geosites that can be used in terms of geotourism in Muş province and its surroundings.

Muş ili ve yakın çevresinde çok sayıda jeoturizm açısından önemli sayılabilecek jeositler mevcuttur. Hamurpet Gölü; oluşumunda etkili olan volkanik ve tektonik olaylar bakımından Muş il sınırları içerisinde kalan önemli jeositlerden biridir. Muş-Varto karayolu üzerinde yer alan fosiller, Bingöl ve Nemrut volkanları, Solhan obsidyen yatakları, Sergen riyolitleri içerisinde yer alan Mercimekkale domu gerek jeolojik geçmişleri ile gerekse kültürel değerleri ile jeoturizm açısından değerlendirilebilecek önemli jeosit alanlarıdır. Kuzey Anadolu ve Doğu Anadolu Fayları yanında Muş Bindirme Zonu (MBZ), Varto Fay Zonu (VFZ) ve bunlar üzerinde yer alan jeolojik ve jeomorfolojik oluşumlar, Muş ili ve yakın çevresinde bulunan diğer jeositlerdir. Muş ili ve yakın çevresinde yer alan jeositlerin değerlendirilmesi ile oluşturulacak jeoparklar; jeolojik güzelliklerin, doğal zenginliklerin, ender oluşumların bulunduğu bir yer olmanın ötesinde yeni bir anlayışla yönetilen ve/veya işletilen alanlara dönüştürülerek sosyo-ekonomik anlamda ile önemli katkılar sunabileceği gibi bu alanların korunması ve gelecek nesillere aktarılmasını sağlayacaktır. Oluşturulacak jeoparklar ilin hem ulusal hem de uluslararası tanıtımına önemli katkı sunacaktır. Bu çalışmada Muş ili ve yakın çevresinde jeoturizm açısından değerlendirilebilecek bazı jeositlerin tanıtılması amaçlanmıştır.
MUŞ İLİ VE YAKIN ÇEVRESİNDE JEOTURİZM AÇISINDAN DEĞERLENDİRİLEBİLECEK JEOSİTLER